2017
DOI: 10.1002/jcb.26302
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin converts Foxp3+ regulatory T cells to T helper 1 cells in patients with lung cancer

Abstract: The regulatory T cells (Treg) play an important role in the tumor tolerance. The methods to regulate the Treg population in cancer-bearing hosts are limited currently. The effect of curcumin on inhibiting cancer has been recognized, but the mechanism remains elusive. This study tests a hypothesis that administration of curcumin down regulates Tregs in lung cancer (LC) patients. In this study, a group of LC patients was treated with curcumin. The peripheral Tregs and T helper (Th) 1 cells were analyzed by flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 34 publications
2
54
0
2
Order By: Relevance
“…For instance, VC positively influences lymphocyte development and function, and enhances T-cell proliferation and T-cell function [14,78]. CC could target regulatory T-cells and convert them into CD4+ Th1 cells to process anti-tumor effects [79,80], and improve the imbalance of Th1/Th2 subsets to process anti-inflammatory and anti-autoimmune effects [27,81]. GA showed anti-allergic effect by restoring the imbalance of Th1/Th2 subsets [82,83].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, VC positively influences lymphocyte development and function, and enhances T-cell proliferation and T-cell function [14,78]. CC could target regulatory T-cells and convert them into CD4+ Th1 cells to process anti-tumor effects [79,80], and improve the imbalance of Th1/Th2 subsets to process anti-inflammatory and anti-autoimmune effects [27,81]. GA showed anti-allergic effect by restoring the imbalance of Th1/Th2 subsets [82,83].…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin can modulate Treg numbers and FoxP3 expression [135]. Decreased numbers of Tregs and increased Th1 cells have been reported in lung cancer patients treated with curcumin [136]. Similar results were seen in colon cancer patients, where curcumin treatment decreased the total number of Tregs and expression levels of FoxP3 as well as increased Th1 cells [137].…”
Section: Curcuminmentioning
confidence: 72%
“…A previous study reported that curcumin inhibits tumor cell apoptosis by downregulating the levels of the tumor immunosuppressive cytokine IL-10, resulting in JAK/STAT signal pathway malfunction (97). Curcumin also downregulates the levels of TGF-β and IL-10 in Treg cells, reduces their ability to stimulated Treg cells and decreases the Treg cell infiltration in tumors (86). An increased expression level of IL-6 in triple-negative breast cancer is considered to mediate the tumor immunosuppressive microenvironment, leading to tumor vaccine therapy failure (98).…”
Section: The Role Of Curcumin In Tumor Immunomodulationmentioning
confidence: 99%